Nanomaterial-based photodynamic therapy for antibacterial applications: a comprehensive review - Gao, Yujie; Lin, Hua; Luo, Yejiao; Li, Jv; Gong, Chen; Chen, Hu; Gong, Renguo (Frontiers in Materials, 2023)
Microbial infections continue to pose a significant health challenge, especially with an increase in drug-resistant bacteria. Conventional antibiotic treatments show limited efficacy, prompting researchers to explore alternative treatments. Photodynamic therapy (PDT) has emerged as a promising alternative that uses reactive oxygen species (ROS) to induce oxidative stress, offering the potential for cyclic treatment without fostering new drug resistance mechanisms. The success of PDT relies heavily on the selection of appropriate photosensitizers (PSs). Various nanomaterials are being developed as PSs or carriers to enhance the efficacy of PDT in the antibacterial field. In this comprehensive review, we discuss the four main ROS generated during PDT and outline their corresponding antibacterial mechanisms. Additionally, we highlight the prominent types of nanomaterials used as PSs or carriers in PDT. We analyze the current challenges associated with nanomaterial-based PDT for antibacterial therapy and propose potential strategies for optimizing their applications.